Experimental and analytical studies of structures seismically isolated with an uplift-restraining friction pendulum system. - Roussis, Panayiotis C.
This paper presents findings from a comprehensive analytical and experimental study on the uplift-restraining XY-FP sliding isolation system. To investigate the effectiveness of the XY-FP isolator and provide a rational basis for evaluating the efficacy of the developed mathematical model, an extensive experimental program was conducted on the earthquake simulator at the University at Buffalo. The experimental program involved a slender, five-storey, scale-model frame seismically isolated with four XY-FP isolators subjected to simulations of historical horizontal and vertical ground motions. The experimental response demonstrates the validity of the concept and provides evidence for the effectiveness of the XY-FP isolator in preventing uplift. A comprehensive analytical model capable of emulating the mechanical behaviour of the XY-FP isolator is developed and implemented in program 3D-BASIS-ME. The newly enhanced program is used to predict the dynamic response of the seismically-isolated model structure. Comparison of analytical predictions with experimental results attests to the efficacy of the analytical model for simulating the response of the XY-FP isolator. With its appealing conceptual simplicity and its proven effectiveness, the new uplift-restraining isolator has the potential to facilitate the application of seismic isolation even under the most extreme of conditions, including but not limited to near-fault strong ground motions and uplift-prone structural systems.
Keywords: Seismic isolation; XY-FP isolator; Experimentation; Uplift-restraint.; Tension; Friction Pendulum